Engenho de memórias: mulheres camponesas, escritas de si e a força da amizade (1975-1984) - Vieira, Jadson Pereira (2016)
Between the years of 1975 and 1984 concerns to historiographical production. Thus, this dissertation brings to light scriptures about the struggling trajectories of Maria de Lourdes de Souza Quincas; Josefa Ermina Cobé Nêm Cobé; Maria do Céu Cobé and Beatriz Pedro da Silva, female community leaders who fought for the rights of rural workers of Engenho Geraldo from Alagoa Nova-PB. They are presented according to a narrative perspective, which objective is building up the history of the struggling years in the community. It is sought to apprehend herein aspects related to those memories belonging to the four female peasant leaders, who acted directly in the struggle for the rights to land ownership promoted by the workers in the community mentioned above. Based on the theoretical support provided on genre debates, by Joan Scott (2006); on self-writings, by M. Foucault and his commentators (1992); on friendship, by F. Ortega (2002) and on memory, by M. Halbwachs (2006), it is intended to contribute to the fortification of social scriptures a possible narrative for further questionings.